Preparation and characterization of an anti-inflammatory agent based on a zinc-layered hydroxide-salicylate nanohybrid and its effect on viability of Vero-3 cells - Ramli, Munirah; Hussein, Mohd Zobir; Yusoff, Khatijah (Dove Medical Press, 2013)
A new organic-inorganic nanohybrid based on zinc-layered hydroxide intercalated with an anti-inflammatory agent was synthesized through direct reaction of salicylic acid at various concentrations with commercially available zinc oxide. The basal spacing of the pure phase nanohybrid was 15.73 Å, with the salicylate anions arranged in a monolayer form and an angle of 57 degrees between the zinc-layered hydroxide interlayers. Fourier transform infrared study further confirmed intercalation of salicylate into the interlayers of zinc-layered hydroxide. The loading of salicylate in the nanohybrid was estimated to be around 29.66%, and the nanohybrid exhibited the properties of a mesoporous-type material, with greatly enhanced thermal stability of the salicylate compared with its free counterpart. In vitro cytotoxicity assay revealed that free salicylic acid, pure zinc oxide, and the nanohybrid have a mild effect on viability of African green monkey kidney (Vero-3) cells.